Restrictions to the Mobility of Companies in the Case-Law of the Court of Justice of the European Union - Sobiech, Agnieszka (Studia Oeconomica Posnaniensia, 2015)
The subject of this study is the problem of the cross-border mobility of companies in the case-law of the Court of Justice of the European Union. Freedom of establishment, expressed in Article 49 of the Treaty on the Functioning of the European Union, guarantees the right to carry out activities in the area of the European Union; not only through subsidiaries, branches, or representative offices, but also directly by moving the headquarters to another Member State. In the absence of secondary legislation governing the procedures for the cross-border relocation of companies, the rulings of the European Court of Justice are of key importance in determining the free migration of companies.